Transforming the Business Studies Curriculum in South African Secondary Schools: Strategies for Developing Entrepreneurial Skills Among Learners - Nzuza, Siyacela Thandazani; Ngwenya, Jabulisile Cynthia (CV Sinergi Ilmu dan Publikasi, 2026)
This study sought to explore teachers’ views on strategies to strengthen the Business Studies curriculum in South African secondary schools in order to equip learners with entrepreneurial skills. While entrepreneurship education has gained global attention, limited research has examined teachers’ perspectives on curriculum transformation within the South African high school context. We employed a qualitative research approach, based on an interpretivist paradigm and case study design, which allowed us to engage directly with participants and obtain an in-depth understanding of their views. The constructivist learning theory frames this study. Semi-structured individual interviews and a focus group interview were employed as primary data collection methods. Participants comprised 10 Business Studies teachers, purposively and conveniently sampled from 10 secondary schools in KwaZulu-Natal. Thematic analysis of the responses revealed an urgent need to improve the business studies curriculum by modernizing it through the integration of digital literacy, establishing an experiential learning component through mentorship and industry partnerships, implementing entrepreneurship as a stand-alone subject, and contextualizing pedagogical strategies in business studies. Drawing from the findings, this study contributes to scholarship on curriculum transformation and provides practical recommendations for policymakers and educators seeking to advance entrepreneurial education in secondary schools.